How sustainable is smart PSS? An integrated evaluation approach based on rough BWM and TODIM. (January 2020) - Liu, Lingdi; Song, Wenyan; Han, Weiwei
Abstract: Smart Product-Service Systems (PSS) integrates smart products and e-services into a total solution with Information and Communication Technology (ICT). It is necessary to assess the Smart PSS from the perspective of sustainability in the early design phase to reduce potential failure to meet the environmental and social requirements in delivery stage. However, the existing PSS evaluation frameworks consider less about characteristics of digitalization and smartness. Moreover, the previous criteria weighting methods for PSS evaluation becomes time consuming and frustrating when comparing too many criteria to determine the weights for criteria. In addition, the existing PSS evaluation methods often omit decision makers' bounded rationality and vagueness of judgements. To solve these problems, a novel method is proposed by integrating the merit of Best Worst Method (BWM) in reducing the decision makers' burden of pairwise comparisons of criteria importance, the strengths of TODIM (an acronym in Portuguese of Interactive and Multi-Criteria Decision Making) in dealing with decision makers' bounded rationality and the flexibility of Rough Set Theory (RST) in handling vagueness without prior information. Finally, a case study of sustainability evaluation for smart air-conditioner PSS is used to validate the effectiveness and efficiency of the proposed method.